2020
DOI: 10.1097/paf.0000000000000555
|View full text |Cite
|
Sign up to set email alerts
|

Can Bone-Specific Alkaline Phosphatase and Osteocalcine Levels Be Used to Determine the Age in Children?

Abstract: Background Demand for age determination by medical methods from legal authorities is of critical importance, especially for people in pubertal age. We planned this study to evaluate the potential utility of biochemical methods in these applications. We aim to investigate whether alkaline phosphatase (ALP), bone-specific alkaline phosphatase (BALP), and osteocalcine can be used in the determination of age. Materials and Methods A total of 146 children (8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…However, it showed no effects on apoptosis, which may be related to the adaptability of cells in hydroxyapatite co culture system. ALP is a biochemical and histological marker to identify osteoblasts, and its activity reflects the differentiation and functional status of osteoblasts to a certain extent [16]. We found that the ALP activity of osteoblasts in hypoxia group was higher than that in normoxia group at 24 h and 48 h, indicating that the differentiation ability of osteoblasts and the bone metabolism of osteoblast like cells under hypoxia condition are more active than that in normoxia condition.…”
Section: Discussionmentioning
confidence: 77%
“…However, it showed no effects on apoptosis, which may be related to the adaptability of cells in hydroxyapatite co culture system. ALP is a biochemical and histological marker to identify osteoblasts, and its activity reflects the differentiation and functional status of osteoblasts to a certain extent [16]. We found that the ALP activity of osteoblasts in hypoxia group was higher than that in normoxia group at 24 h and 48 h, indicating that the differentiation ability of osteoblasts and the bone metabolism of osteoblast like cells under hypoxia condition are more active than that in normoxia condition.…”
Section: Discussionmentioning
confidence: 77%
“…Tissue-nonspecific ALP is a routinely used biochemical index in bone formation, which plays an important role in the early mineralization of the ECM . ALPL is the gene encoding tissue-nonspecific ALP.…”
Section: Resultsmentioning
confidence: 99%